Salmonella enterica Elicits and Is Restricted by Nitric Oxide and Reactive Oxygen Species on Tomato - Ferelli, Angela Marie C.; Bolten, Samantha; Szczesny, Brooke; Micallef, Shirley A. (Frontiers in Microbiology, 2020)
The enteric pathogen Salmonella enterica can interact with parts of the plant immune system despite not being a phytopathogen. Previous transcriptomic profiling of S. enterica associating with tomato suggested that Salmonella was responding to oxidative and nitrosative stress in the plant niche. We aimed to investigate whether Salmonella was eliciting generation of reactive oxygen species (ROS) and nitric oxide (NO), two components of the microbe-associated molecular pattern (MAMP)-triggered immunity (MTI) of plants. We also sought to determine whether this interaction had any measurable effects on Salmonella colonization of plants. Biochemical, gene expression and on-plant challenge assays of tomato vegetative and fruit organs were conducted to assess the elicitation of ROS and NO in response to Salmonella Newport association. The counter bacterial response and the effect of NO and ROS on Salmonella colonization was also investigated. We detected H2O2 in leaves and fruit following challenge with live S. Newport (p<0.05). Conversely, NO was detected on leaves but not on fruit in response to S. Newport (p<0.05). We found no evidence of plant defense attenuation by live S. Newport. Bacterial gene expression of S. Newport associating with leaves and fruit were indicative of adaptation to biotic stress in the plant niche. The nitrosative stress response genes hmpA and yoaG were significantly up-regulated in S. Newport on leaves and fruit tissue compared to tissue scavenged of NO or ROS (p<0.05). Chemical modulation of these molecules in the plant had a restrictive effect on bacterial populations. Significantly higher S. Newport titers were retrieved from H2O2 scavenged leaves and fruit surfaces compared to controls (p<0.05). Similarly, S. Newport counts recovered from NO-scavenged leaves, but not fruit, were higher compared to control (p<0.05), and significantly lower on leaves pre-elicited to produce endogenous NO. We present evidence of Salmonella elicitation of ROS and NO in tomato, which appear to have a restricting effect on the pathogen. Moreover, bacterial recognition of ROS and NO stress was detected. This work shows that tomato has mechanisms to check Salmonella populations and ROS and NO detoxification may play an important role in Salmonella adaptation to the plant niche.